Organization, expectations and longings: The experience of the Cooperative Jesus Solidario in The Coipa, Cajamarca - Pompilla Pérez, Yhojan (2017)
The article studies the case of the Jesús Solidario Cooperative, a small cooperative of coffee producers in northern Peru, created with Christian values. The article discusses if it can be considered as an example of social economy, alternative to capitalism, as well as the tensions that it faces in the process of its growth and consolidation.